Transgender Tapestry: celebrating the diversity of gender expression (Wayland: Inernational Foundation of Gender Education)
"Fonds Suzan Daniel (FSD)Periodiciteit: driemaandelijksRedactie: PO Box 367, Wayland, MA 01778"